Field degradation of aminopyralid and clopyralid and microbial community response to application in Alaskan soils. (8th January 2016) - Tomco, Patrick L.; Duddleston, Khrystyne N.; Schultz, Emily Jo; Hagedorn, Birgit; Stevenson, Timothy J.; Seefeldt, Steven S.
Abstract: High‐latitude regions experience unique conditions that affect the degradation rate of agrochemicals in the environment. In the present study, data collected from 2 field sites in Alaska, USA (Palmer and Delta) were used to generate a kinetic model for aminopyralid and clopyralid degradation and to describe the microbial community response to herbicide exposure. Field plots were sprayed with herbicides and sampled over the summer of 2013. Quantification was performed via liquid chromatrography/tandem mass spectrometry, and microbial diversity was assessed via next‐generation sequencing of bacterial 16S ribosomal ribonucleic acid (rRNA) genes. Both compounds degraded rapidly via pseudo‐first–order degradation kinetics between 0 d and 28 d ( t 1/2  = 9.1–23.0 d), and then degradation slowed thereafter through 90 d. Aminopyralid concentration was 0.048 μg/g to 0.120 μg/g at 90 d post application, whereas clopyralid degraded rapidly at the Palmer site but was recovered in Delta soil at a concentraction of 0.046 μg/g. Microbial community diversity was moderately impacted by herbicide treatment, with the effect more pronounced at Delta. These data predict reductions in crop yield when sensitive plants (potatoes, tomatoes, marigolds, etc.) are rotated onto treated fields. Agricultural operations in high‐latitude regions, both commercial and residential, rely heavily on cultivation of such crops and care must be taken when rotating. Environ Toxicol Chem 2016;35:485–493. © 2015 SETAC